Pengaruh Pertumbuhan Ekonomi dan Persentase Jumlah Penduduk yang Menganggur Terhadap Kemiskinan di Indonesia Tahun 2016-2020 - Pande Nyoman Natasha Deswari; A. A. Ketut Jayawarsa; I Gusti Ayu Athina Wulandari (Warmadewa Economic Development Journal (WEDJ), 2023)
This research was conducted based on the gap in the results of previous research (research gap) and differences in focus on economic growth and the percentage of the unemployed population to poverty. In addition, there is also a research problem (gap phenomenon) regarding poverty in Indonesia which is still quite high, even though the government has implemented programs to alleviate poverty. However, this does not have a significant impact on poverty reduction in Indonesia. This study aims to analyze the effect of population growth and the number of unemployed people on poverty. All data in this study were obtained through the official website of the Central Bureau of Statistics, then analyzed using panel data regression analysis and hypothesis testing (T test, F test and coefficient of determination test). The results of the research shows that (1) economic growth has a positive and significant effect on poverty, (2) the number of unemployed people has a positive and significant effect on poverty, (3) economic growth and the number of unemployed people simultaneously have an effect on poverty.